2018
DOI: 10.1002/mnfr.201800535
|View full text |Cite
|
Sign up to set email alerts
|

Goji Berry Modulates Gut Microbiota and Alleviates Colitis in IL‐10‐Deficient Mice

Abstract: Scope This study examines the beneficial effects of Goji berry against spontaneous colitis and its prebiotic role in IL‐10‐deficient mice. Methods IL‐10‐deficient mice are assigned to a standard rodent diet (control) or a control diet supplemented with Goji (1% of dry feed weight) for 10 weeks, at which point colonic tissues and fecal contents are collected. Results Goji supplementation decreases colonic pathobiological scores and mRNA expression of Il17a and Tgfb1, while it enhances Muc1 expression and fecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 58 publications
3
47
0
Order By: Relevance
“…An open pilot trial demonstrated that a daily standardized anthocyanin-rich bil-Digestion 2020;101(suppl 1):120-135 DOI: 10.1159/000505368 berry preparation in mild to moderate UC patients achieved remission and response in 63.7 and 90.9%, respectively, after 6 weeks. Additionally, goji berry, another traditional supplement, has been shown to promote butyrate-producing bacteria and Bifidobacteria in interleukin-10-deficient mice, which in turn results in the suppression of intestinal inflammation [147].…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…An open pilot trial demonstrated that a daily standardized anthocyanin-rich bil-Digestion 2020;101(suppl 1):120-135 DOI: 10.1159/000505368 berry preparation in mild to moderate UC patients achieved remission and response in 63.7 and 90.9%, respectively, after 6 weeks. Additionally, goji berry, another traditional supplement, has been shown to promote butyrate-producing bacteria and Bifidobacteria in interleukin-10-deficient mice, which in turn results in the suppression of intestinal inflammation [147].…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…In another study, dietary GB supplementation also increased health-promoting secondary metabolite and SCOA-producing Actinobacteria , Lachnospiraceae , Clostridium XIVb, Sporobacter , Pseudoflavonifractor , Butyriccicoccus , Anaerotruncus, Anaerosporobacter, and Ruminococcaceae populations without affecting Akkemansia , Mucispirillum , Bacteriodes , and Desulfovirio . Butyryl-Coenzyme A CoA transferase is an important butyrate gene, and GBPS supplementation increased its expression in butyrate-producing bacteria such as the Clostridium cluster XIVa group including Lachnospiraceae , Faecailbacterium prausnitzii, and Ruminococcaceae [ 164 ]. The GBPS prebiotic effects increased the populations of Firmicutes , Akkermansia , Proteobacteria , Lactobacillus , and Prevotellaceae [ 165 ].…”
Section: Goji Berriesmentioning
confidence: 99%
“…In fact, there are a lot of evidences showing that the berry has numerous potential beneficial effects for the general well-being of the individual and for the prevention and treatment of numerous pathologies [1][2][3][4]. Beside several biological active compounds such as carotenoids, vitamins (riboflavin, thiamin and ascorbic acid) and flavonoids, goji berry is primarily rich in polysaccharides [1] which are responsible for the main beneficial pharmacological effects of the fruit both in vitro [5][6][7][8] and in vivo in various laboratory animal species [9,10] and in clinical trials in humans [11,12]. The effects of the goji berries are mainly studied in laboratory animals such as mice and rats [9,10,13] and only a few trials were conducted using the rabbit [14][15][16] although it is considered a useful experimental animal model [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Beside several biological active compounds such as carotenoids, vitamins (riboflavin, thiamin and ascorbic acid) and flavonoids, goji berry is primarily rich in polysaccharides [1] which are responsible for the main beneficial pharmacological effects of the fruit both in vitro [5][6][7][8] and in vivo in various laboratory animal species [9,10] and in clinical trials in humans [11,12]. The effects of the goji berries are mainly studied in laboratory animals such as mice and rats [9,10,13] and only a few trials were conducted using the rabbit [14][15][16] although it is considered a useful experimental animal model [17][18][19][20][21][22]. Moreover, only a limited number of researches evaluated the effects of goji berry on the reproductive and productive performance, other than on the quality of meat, in livestock animals, rabbits included [15,16,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%